Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Consider the equation below:

-2(2x - 5) = 18

The value of x in terms of b is [tex]$\square$[/tex]

The value of x when b is 3 is [tex]$\square$[/tex]


Sagot :

Sure, let's solve the equation step-by-step.

Given equation:

[tex]\[ -2(2x - 5) - 18 = 0 \][/tex]

First, distribute the -2 across the parentheses:

[tex]\[ -2 \cdot 2x - (-2 \cdot 5) - 18 = 0 \][/tex]

This simplifies to:

[tex]\[ -4x + 10 - 18 = 0 \][/tex]

Combine the constants:

[tex]\[ -4x - 8 = 0 \][/tex]

Next, isolate [tex]\( x \)[/tex] by adding 8 to both sides:

[tex]\[ -4x = 8 \][/tex]

Then, divide both sides by -4:

[tex]\[ x = -2 \][/tex]

So, the value of [tex]\( x \)[/tex] is:

[tex]\[ x = -2 \][/tex]

Now, let's find the value when [tex]\( b = 3 \)[/tex]. Here, interpret the equation [tex]\( -2(2x - 5) - 18 = 0 \)[/tex] in terms of [tex]\( b \)[/tex]:

First, substitute [tex]\( b = 3 \)[/tex] into the equation. This yields:

[tex]\[ -2(2 \cdot 3 - 5) - 18 \][/tex]

Calculate inside the parentheses first:

[tex]\[ 2 \cdot 3 = 6 \][/tex]

[tex]\[ 6 - 5 = 1 \][/tex]

Now, replace the simplified terms back into the equation:

[tex]\[ -2 \cdot 1 - 18 \][/tex]

Multiply:

[tex]\[ -2 \cdot 1 = -2 \][/tex]

Finally,

[tex]\[ -2 - 18 = -20 \][/tex]

Now, negating -20, we have:

[tex]\[ 20 \][/tex]

So, when [tex]\( b = 3 \)[/tex]:

[tex]\[ x = 20 \][/tex]

Thus, the complete answers are:

- The value of [tex]\( x \)[/tex] is [tex]\( -2 \)[/tex].
- The value of [tex]\( x \)[/tex] when [tex]\( b = 3 \)[/tex] is [tex]\( 20 \)[/tex].